IMPLEMENTATION OF RESPONDENT DATA PROTECTION POLICY IN THE IMPLEMENTATION OF STATISTICAL ACTIVITIES AT BPS TOMOHON CITY - Irfan Damar Prasetyo; Fredinand Kerebungu; Recky H. E. Sendouw (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study discusses the implementation of respondent data protection policy in the implementation of statistical activities at the Central Statistics Agency (BPS) of Tomohon City, with a focus on the dimension of data confidentiality as mandated in Law Number 16 of 1997 concerning Statistics and Law Number 27 of 2022 concerning Personal Data Protection. The purpose of this study is to describe, analyze, and explain the implementation of respondent data confidentiality policy and identify supporting and inhibiting factors in the implementation of the policy at BPS of Tomohon City. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews with six informants consisting of leaders, permanent employees, and statistical partners of BPS of Tomohon City, and supported by documentation studies. Data analysis was carried out using the interactive model of Miles, Huberman, and Saldana, with data validity testing through triangulation and member checks . The results of the study indicate that the implementation of respondent data protection policy at BPS of Tomohon City faces a shift in meaning from normative to pragmatic, especially at the statistical partner level. Although the multi-layered oversight system has been functioning well, the lack of technical Standard Operating Procedures (SOPs) and standard communication scripts has led to the emergence of "Cultural SOPs" and improvised communication in the field. The main supporting factors are a centralized data processing system and support from local authorities. Meanwhile, inhibiting factors include low legal literacy among statistical partners, minimal regulatory outreach, and public resistance dominated by tax concerns and perceived privacy risks, particularly among educated groups.